Health inequalities, welfare state regimes and economic crisis: A comparative analysis in Sweden, Greece and Poland - Stefania Kalogeraki (Journal of Health and Social Sciences)
Introduction: The aim of this paper is to explore individual-level determinants of health inequalities across three European countries (Sweden, Greece and Poland) with different welfare systems and differently affected by the recent economic crisis. Methods: The data derived from an original cross-national survey conducted in the context of the EU-funded LIVEWHAT project. The Chi-Square Test of Independence was used to examine potential differences in specific demographic traits, in socio-economic status and living conditions as well as in bridging and bonding social capital between individuals reporting poor health across Sweden, Greece and Poland. Binary logistic regression models were used to predict poor self-rated health based on the aforementioned predictors in the three countries under study. Results: Poor self-rated health was more prevalent in Poland (42.8%), the lowest prevalence rate was in Sweden (30.4%) followed by Greece (31.9%). The Chi-Square Test of Independence indicated significant differences between respondents reporting having poor health across the three countries with respect to their demographic characteristics, socio-economic status, socio-economic living conditions, and bridging social capital. The binary logistic regression analysis showed that specific indicators of lower socio-economic status and of adverse living conditions were more strongly associated with poor self-rated health in Greece and Poland, whereas individual traits associated with socio-economic living conditions were less important in predicting poor self-rated health in Sweden when taking into account individuals’ bridging and bonding social capital. Overall the lack of different forms of social capital was more strongly related to poor self-rated health in Sweden than in the other two countries. Discussion and Conclusion: Material explanations might be relatively more important in elucidating health outcomes in contexts with less generous welfare states, which were more severely affected by the recent economic crisis such as Greece and Poland, whereas social capital might be more decisive for health outcomes in a wealthy country with a universal welfare state such as Sweden.